Understanding Function and Performance of Carbon Additives in Lead-Acid Batteries. Issue 13 (1st January 2017) - Enos, D. G.; Ferreira, S. R.; Barkholtz, H. M.; Baca, W.; Fenstermacher, S.
Abstract : While the low cost and strong safety record of lead-acid batteries make them an appealing option compared to lithium-ion technologies for stationary storage, they can be rapidly degraded by the extended periods of high rate, partial state-of-charge operation required in such applications. Degradation occurs primarily through a process called hard sulfation, where large PbSO4 crystals are formed on the negative battery plates, hindering charge acceptance and reducing battery capacity. Various researchers have found that the addition of some forms of excess carbon to the negative active mass in lead-acid batteries can mitigate hard sulfation, but the mechanism through which this is accomplished is unclear. In this work, the effect of carbon composition and morphology was explored by characterizing four discrete types of carbon additives, then evaluating their effect when added to the negative electrodes within a traditional valve-regulated lead-acid battery design. The cycle life for the carbon modified cells was significantly larger than an unmodified control, with cells containing a mixture of graphitic carbon and carbon black yielding the greatest improvement. The carbons also impacted other electrochemical aspects of the battery (e.g., float current, capacity, etc.) as well as physical characteristics of the negative active mass, such as the specific surface area.